Research on Incorporating Creative Design into Teaching Process -Taking Casual Clothing Creation as an Example - Chin, Lin Chin-Min; Lin, Jia Ru (IJRDO - Journal of Social Science and Humanities Research, 2020)
In the modern era, people pay attention to the quality of leisure life in addition to busy work, individuality and fashion style leisure activities also led to a display of self-style casual clothing the best performance. Based on the principles of this exquisite casual clothing pleasure and creative design.the characteristic trait of casual clothing design is that more exquisite materials and finer workmanship. Moreover, more elements of high-class fashion clothing and fashion trends are integrated into design of details and the style of the designs is minimalism and practicality. Pure silk fabrics, which boast a good quality, are adopted to present the quality of the garments. Printed fabrics are used as the prime design pattern. As for the use of colors, the purplish blue and white dominant colors are embellished by a sprinkle of the light gold color to make the products exude an elegant, neat and chic, low-key luxury, and carefree aura. The design is simple yet elegant. Therefore, uphold the "less is more" principle of the pursuit of simple but refined design, complete four creative casual wear design cases include: "Calm", "Elegant", "Energetic", "Neat" to let leisure time Creative costumes, not only is designed for specific groups tailored and combined leisure and entertainment and youthful characteristics, so casual clothing show the fashion appearance and life aesthetics.